EVALUATION OF A BEACH VOLLEYBALL SKILL INSTRUMENT FOR THE LINE SHOT ATTACK - George Giatsis; Afroditi Lola; Dimitris Hatzimanouil; George Tzetzis (Journal of Physical Education)
ABSTRACT This study aimed to develop a test for measuring athletes’ performance. Logical, content, construct, criterion validity, as well as reliability, were examined. Three beach volleyball experts evaluated how well the test evaluates the shot skill accuracy according to their judgment (logical validity). A group of eight beach volleyball experts analyzed the test and rated it on a scale of 1 to 7 regarding the relevance of the content as a measure of beach volleyball athlete’s accuracy, the average score was calculated at 6.75 (SD=0.46) (content validity). 60 beach volleyball players divided into three equal groups of novices, intermediates, and experts were asked to undergo the test on two separate days. A one-way ANOVA between the three groups was performed, which indicated that the mean scores of the three groups differed significantly (p<0.001 for both days): experts achieved better scores than intermediates who in turn scored better than novices (construct validity). The athletes’ scores were correlated with their proficiency level, using the Pearson Correlation test, which indicated very high positive (Day-1: r=0.956, n=60, p<0.001; Day-2: r=0.953, n=60, p<0.001) (criterion validity). The intraclass correlation coefficient was calculated between Day-1 and Day-2 and was found equal to 0.980 for average measures (p<0.001) and 0.961 for single measures (p<0.001). In conclusion, the requirements for logical, content, construct, criterion validity, and reliability have been met. Therefore, the line shot attack test can be used as a valid and reliable measurement instrument for evaluating the performance of beach volleyball athletes.